Pelembagaan Pembaharuan Pengelolaan Program KIA (Kesehatan Ibu dan Anak) Analisis Pengaruh Variabel Internal dan Eksternal Institusi dalam Pelembagaan Pembaharuan Pengelolaan Program KIA di Bakorwil Madura - * Hermanoadi (DIA: Jurnal Administrasi Publik, 2012)
Development covered the effort of change and innovation in society or nation life aspect to achieveÂ  from one situation to another situation to more better. Include health sector.Another indicator of health sector succsess is Baby Mortality Rate. The Baby Mortality Rate in Indonesia about 24 per 1000 life birth in 2009. The baby mortality rate mentioned high enough if compared with ASEAN satate. For coping the problem of mother and baby health In Indonesia, so the role of KIA program (Program Kesehatan Ibu dam Anak) in the Society Health Center (Puskesmas) is very importen. This research useÂ  Milton J. Esman concept (1971). This concept suggest that two groups of variables or factos are important to understanding and guiding institution building activity. These are the â€œinstitution variablesâ€, which are assentially concern with the organization it self. TheÂ  institution variable include leadership, doctrine, program, resources and internal structure. And the â€œlinkage variablesâ€ mainly to external relation. TheÂ  linkage variable include enabling linkages, functional linkages, normative linkages and diffused linkages.The goals of this research are to examineÂ  wheather: leadership, doctrine, program, resources and internal structure affect the institutionalization of mother and baby health in Bakorwil Madura. And also to examine wheather enabling linkages, functional linkages and local culture value affect the institutionalization of mother and baby health in Bakorwil Madura. The result of quantitative analysis showed that: leadership, doctrine, program, resources and internal structure affect the institutionalization of mother and baby health in Bakorwil Madura. And also enabling linkages, functional linkages and local culture value affect the institutionalization of mother and baby health in Bakorwil Madura. Nevertheless, if investigate from b coefficient all variable and t statistic all variable showed thatÂ  resources,Â  leadership, local culture value and enabling linkages are critical variables. Key Words: The institutionalization of program managing modernity, human develop-ment index, The program of health mother and baby